Biomechanical analysis of different starting strategies utilized during cross-country skiing starts - Wennemar Wiltmann, V.; Holmberg, H. C.; Pelttari, P.; Mikkola, J.; Häkkinen, K.; Ohtonen, O.; Linnamo, V. (European Journal of Sport Science, 2016)
The present study was designed to analyse and compare the kinetics and kinematics associated with three different starting strategies during classic cross-country ski racing. Inside a ski tunnel, 12 elite male skiers performed three sets of three 38 m starts. Each set included one start using: double poling only (DP), diagonal stride only (DIA) and freely chosen (FREE) (i.e. where subjects used the strategy or combination of strategies they felt was fastest) in random order. The first 18 m was performed on a series of force plates that measured horizontal and vertical forces followed by 20 m of a standard snow track. Additionally, cycle characteristics and joint angles were measured. DIA and FREE were faster over 38 m than DP (P < .01). Net horizontal impulse (taking into account both positive and negative impulses) 5-10 m after the start was lower during DP than during DIA and FREE (both P < .05). All subjects skied faster when using only DIA for the entire 38 m. Furthermore, the sum duration and frequency of propulsive contacts over the first 18 m was less in DP than DIA and FREE (P < .01). In conclusion, differences between the starting strategies examined was especially pronounced during the initial cycles. Transition from DIA to DP during the start also slowed the skiers, but optimal timing for such a transition was not elucidated.